Perceived discrimination as a mediator between cultural identity and mental health symptoms among racial/ethnic minority adults in the United States: insights from the Health Information National Trends Survey 6 - Zhou, Lulin; Nutakor, Jonathan Aseye; Larnyo, Ebenezer; Addai-Dansoh, Stephen; Cui, Yupeng; Dey, Nutifafa Eugene Yaw (Frontiers in Psychology, 2024)
Objective This study examined the role of perceived discrimination as a mediator between cultural identity and mental health symptoms among adults from racial/ethnic minority groups in the United States. Methods Data were gathered from the National Cancer Institute’s (NCI) Health Information National Trends Survey (HINTS) 6, a nationally representative survey. The mediating role of perceived discrimination was investigated using structural equation modeling (SEM) analysis. Results The study found significant associations between demographic and lifestyle factors and mental health symptoms. Non-Hispanic Blacks or African Americans and Hispanics were less likely than Non-Hispanic Whites to have mental health symptoms. Individuals between the ages of 35 and 49, 50 to 64, 65 to 74, and 75 and older had lower odds of mental health symptoms. Gender differences revealed that females had a higher risk of mental health issues than males. Socioeconomic factors, such as household income and employment status, played a significant role, with higher household income and employment status being associated with a decreased likelihood of mental health symptoms. The study emphasizes the role of perceived discrimination as a mediator, suggesting that it fully mediated the association between cultural identity and mental health symptoms. These findings highlight the significance of addressing discrimination experiences in fostering the mental health of adults from diverse backgrounds. Conclusion The findings highlight the need to take racial, ethnic, and socioeconomic inequities, as well as cultural identity and prejudice, into account in mental health research and interventions. The identified risk and protective factors can guide interventions and policies to enhance this population’s mental health.